Growth Performance of Broilers fed Basal Diets with Different Nutrient Content and Added with Enzyme - Anu, Yahana; Nalle, Catootjie Lusje; Sabuna, Cytske (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2024)
The balance of nutrients in the diet is essential for optimal bird performance. The purpose of the present study was to evaluate the growth response of broilers fed different basal diets supplemented with enzymes. A total of 250 day-old chicks (Cobbs, mixed sex) were used in this experiment. The experiment was designed using a completely randomized design (CRD) consisting of 5 treatments and 5 replications (10 birds/pen). The treatments were as follows: P0 = control diets, P0= Control diets, P1= Low crude protein diets (PK) P2= Low crude protein diets supplemented with protease; P3= Low phosphor diets; P4= Low phosphor diets supplemented with fitase. The results of statistical analysis showed that treatment had a significant effect (P<0.05) on feed intake, body weight gain (BWG), and feed conversion ratio(FCR) of broiler chickens aged 3 weeks. The conclusion of this study was that the addition of protease in a low-protein diet enhances feed intake, body weight gain, and feed efficiency in starter phase broilers. Conversely, the addition of phytase in a low-phosphorus and low-protein diet does not improve the growth performance of starter phase broilers.